2020
DOI: 10.1139/cgj-2018-0583
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects on mechanical behaviour of soil–structure interface

Abstract: 8The mechanical behaviour of the soil-structure interface plays a major role in the shear 9 characteristics and bearing capacity of foundations. In thermo-active structures, due to 10 non-isothermal conditions, the interface behaviour becomes more complex. The objective 11 of this study is to investigate the effects of temperature variations on the mechanical 12 behaviour of soils and soil-structure interface. Constant normal load (CNL) and constant 13 normal stiffness (CNS) tests were performed on soil and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 28 publications
3
23
0
3
Order By: Relevance
“…Thermally induced hardening of NC clay-concrete interface was found to be minor at a low normal stress (150 kPa), while it was significant at higher normal stresses (225 and 300 kPa). Among these studies, the experimental results of Maghsoodi et al (2020b) are presented in the following. Fig.…”
Section: Features Of Thermo-mechanical Behavior Of Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermally induced hardening of NC clay-concrete interface was found to be minor at a low normal stress (150 kPa), while it was significant at higher normal stresses (225 and 300 kPa). Among these studies, the experimental results of Maghsoodi et al (2020b) are presented in the following. Fig.…”
Section: Features Of Thermo-mechanical Behavior Of Soilsmentioning
confidence: 99%
“…They concluded that the shear stress increase in the clay-structure interface could be due to thermally induced overconsolidation of normally consolidated clay. To support this statement, data from Maghsoodi et al (2020b) are provided. Fig.…”
Section: Features Of Thermo-mechanical Behavior Of Soilsmentioning
confidence: 99%
“…In such a setup, the temperature of the fully saturated shear box container can be controlled by three thermocouples, one in the lower half of the shear box, another on the upper half of the shear box and the last one in the container. The device can be programmed either in stress or deformation controlled tests (Maghsoodi et al 2019b). The lower half shear box is displaced horizontally to apply the shear.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Regarding the impact of temperature on the soil-structure interface, some experimental studies have been performed (Di Donna et al 2015;Yavari et al 2016;Li et al 2018;Maghsoodi et al 2019b;Yazdani et al 2019) In this context, this study was focused on the one-way cyclic behavior of clay-structure interface under isothermal or non-isothermal conditions. The effects of two parameters on strain accumulation, excess pore water pressure and cyclic degradation were more specifically considered.…”
Section: Introductionmentioning
confidence: 99%
“…The number of cycles to failure increased for heated samples due to the densification of clay under drained heating and also the pore pressure of heated samples was slightly less than unheated ones. Regarding the impact of temperature on the soil-structure interface, some experimental studies have been performed [9,16,17] on direct shear device and concerning the in-situ behavior; [18] have developed a thermal borehole shear device to study effect of temperature on the in situ shear behavior of soil-concrete interfaces, but to the knowledge of the authors very few studies have been carried out on the thermal effects on the cyclic behavior of clay-structure interface. [9] performed cyclic constant normal stiffness (CNS) two-way strain controlled tests at different temperatures on illite clay.…”
Section: Introductionmentioning
confidence: 99%